2023
DOI: 10.1021/acs.jchemed.2c00844
|View full text |Cite
|
Sign up to set email alerts
|

Course-Based Undergraduate Research Experiences as a Community of Practice (CoP)

Abstract: Course-based Undergraduate Research Experiences (CUREs) are a pedagogical model where a traditional undergraduate course is transformed into a research-intensive course, offering an alternative pathway to research for undergraduate students. Given the novel learning context of CUREs, there is a need to understand the learning that occurs and the impact of social interactions on students in defining and managing the socially negotiated understandings and practices of the science research laboratory. This manusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Buchanan and Fisher also point to the need to examine CUREs for the presence of SEPs, which could strengthen claims about whether CUREs provide an authentic environment for the development of situated cognition about authentic science . This will complement the recent paper in the Journal by Walker et al that examined CUREs from the framework of a Community of Practice, originally developed by Lave and Wenger. , …”
Section: Theoretical Frameworkmentioning
confidence: 71%
See 1 more Smart Citation
“…Buchanan and Fisher also point to the need to examine CUREs for the presence of SEPs, which could strengthen claims about whether CUREs provide an authentic environment for the development of situated cognition about authentic science . This will complement the recent paper in the Journal by Walker et al that examined CUREs from the framework of a Community of Practice, originally developed by Lave and Wenger. , …”
Section: Theoretical Frameworkmentioning
confidence: 71%
“…Our work to understanding CUREs through the use of established practice frameworks offers a complementary approach to that employed by Walker et al, who examined CUREs relative to the Community of Practice framework presented by Lave and Wenger. , We are examining CURES relative to SEPs. They used focus groups as a source of data for student experiences and analyzed them with respect to the framework of a Community of Practice as formulated by Lave and Wenger.…”
Section: Discussionmentioning
confidence: 99%
“…Key skills that biochemistry students should have upon completing their degree are the ability to interpret experimental data, use computers as information and research tools, and use oral, written, and visual means to present their work. , Students in a traditional biochemistry lecture course often do not achieve proficiency in these key skills. One way for students to gain proficiency at these important skills is to participate in a course-undergraduate research experience (CURE), an in-class activity that mimics the characteristics of mentored undergraduate research through features like exploring the primary literature, working independently and/or collaboratively, and effectively communicating findings from the project. Undergraduate research is classified as a high-impact practice but due to the ratio of faculty to undergraduate students, many students are not able to participate in traditional faculty-mentored research . CUREs have been implemented to give more students an authentic research experience as part of their in-class experience, which has been shown to improve engagement and persistence in STEM. CUREs are generally characterized by involving (1) the use of scientific practices, (2) discovery, (3) broadly relevant or important work, (4) collaboration, and (5) iteration. , …”
Section: Introductionmentioning
confidence: 99%